2019
DOI: 10.1039/c9ja00027e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of major and trace elements in geological samples by laser ablation solution sampling-inductively coupled plasma mass spectrometry

Abstract: Water-related interferences and matrix effects in ICP-MS are dramatically reduced by using laser ablation solution sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The detection limits reported by the direct liquid ablation were 0.01–1 ng g −1 (46 elements in 2% (v/v) HNO 3 ). 15 The DSS-based method similarly reported detection limits of 0.04–0.54 ng g −1 (Co, Cu, Cd and Pb in blood). 20 Therefore, the detection limit was comparable to previous studies.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The detection limits reported by the direct liquid ablation were 0.01–1 ng g −1 (46 elements in 2% (v/v) HNO 3 ). 15 The DSS-based method similarly reported detection limits of 0.04–0.54 ng g −1 (Co, Cu, Cd and Pb in blood). 20 Therefore, the detection limit was comparable to previous studies.…”
Section: Resultsmentioning
confidence: 95%
“…Direct liquid ablation has been reported for aqueous samples. 15,16 However, the preparation of a sealed sample with a lm is needed to suppress the evaporation of sample solution in the ablation cell.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid targets were prepared by pipetting ∼65 μL of each solution sample into the tiny holes drilled on a Teflon sheet and subsequently sealed with a parafilm “M” laboratory film (Bemis Company, Inc.). The solution samples were ablated in a static (single spot) mode, but a scanning mode (2 μm s –1 ) was employed for solid samples due to a decaying transient signal generated with the gradually deepening ablation crater. , Each data acquisition took about 80 s, 20 s for background intensity and 50 s of measurement time, wherein a 40 s stable signal interval was integrated for isotope ratio determination (Figure S1). The background was averaged after the exclusion of measurements that deviated by 2SD (standard deviation).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…In addition, to correct instrument mass bias, a sample solution is usually required to match closely to the external standard in both the analyte concentration and the matrix, especially when a simple sample-standard bracketing method is used for calibration. 7 In a recent study, 8 an enormous reduction in matrix effects for elemental analysis was reported using LA-ICP-MS and solution-based sample introduction. Therefore, isotopic analysis may be possibly free from a rigorous purification process by LA solution sample introduction MC-ICP-MS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rare earth elements (REE) are generally probed with destructive techniques such as ICPMS, LA-ICPMS, , HR-ICPMS, MC-ICPMS, or ICP-AES, possibly combined with specialized sample preparation methods. The destructive character of these techniques causes at least partially destroyed samples which is a major disadvantage when unique samples are examined.…”
mentioning
confidence: 99%